Cloning, sequencing, and characterizing of soil antibiotic active-producing Streptomyces species-specific DNA markers - Saadoun, Ismail (2023)
Association of the antibiotic activity of the soil Streptomyces isolates to their genetic profiles analyzed through RAPD-PCR fingerprints prompted us here in this study to use the most common bands as specific markers to identify homologous proteins within these isolates by cloning, sequencing, and characterizing these markers. Six out of twelve DNA bands ranged between 600 and 1350 bp previously obtained by RAPD-PCR analysis were purified out of the RAPD gels, and then cloned into pGEM-T Easy vector system. Success of the cloning process was confirmed by digesting purified plasmids with EcoRI. The clones namely No. 54, 55, 20, 56, 57, and 58 were sequenced using the DNA BigDye Terminator Sequencing System utilizing the M13 primer. Results indicated that the size of the inserted sequences is 599, 566, 522, 870, 857, and 254 bp, in clones No. 54. 55, 20, 56, 57, and 58, respectively. Homologous proteins of the six cloned sequences generated by DNA blast software indicated that the highest score of protein homology was scored for clone No. 54 with 87 % homology to putative secreted pectate lyase [Streptomyces coelicolor A3(2)]. The other clones showed less homology with 77 % homology for the clones No. 55 and 56, 73 % homology for the clone No. 20, and 55 % homology for the clones No. 57 and 58. The association of homologous proteins to the reported RAPD pattern is confirmed here for the first time, and the resulting DNA cloned fragments deserve further molecular analysis.